2011
DOI: 10.1021/cg2005387
|View full text |Cite
|
Sign up to set email alerts
|

Design and Growth of Quaternary Mg and Ga Codoped ZnO Thin Films with Transparent Conductive Characteristics

Abstract: This study reports the design growth and characterization of quaternary Mg and Ga codoped ZnO (MGZO) thin films with transparent conductive characteristics deposited on glass substrates by RF magnetron sputtering. The effects of the Ga concentration (from 0 to 2 at %) on the structural, chemical, morphological, optical, and electrical properties of MGZO thin films were investigated. X-ray diffraction study showed that all the MGZO thin films were grown as a polycrystalline hexagonal wurtzite phase with a c-axi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…As an alternative, MgZnO:Ga TCO has been researched for available band-gap engineering through Mg concentration [9,10]. By alloying MgO into the ZnO layer, the optical transmission can increase in the near ultraviolet and visible region.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative, MgZnO:Ga TCO has been researched for available band-gap engineering through Mg concentration [9,10]. By alloying MgO into the ZnO layer, the optical transmission can increase in the near ultraviolet and visible region.…”
Section: Introductionmentioning
confidence: 99%
“…In order to resolve the dilemma, the incorporation of Mg ang Gropu-III elements into ZnO will be a good selection due to the widened optical band gap and electrical conduction [7][8][9][10][11]. Furthermore, first-principles investigations based on density…”
Section: Introductionmentioning
confidence: 99%
“…Among them, Ga has recognized as the most promising candidate due to its chemical stability and strong resistant to oxidation as well as matched ionic size and covalent radii of 0.62 Å and 1.26 Å with Zn (0.60 Å, 1.25 Å), which ensure the smaller lattice distortion [7][8][9] and it has been demonstrated that a low resistivity of $10 À4 O cm can be realized from the Ga-doped ZnO films, which is comparable with that of ITO [10,11]. While, TCO materials with a wider band-gap for application in optoelectronic devices operating in the ultra violet (UV) regime are strongly required, as an operating regime of optoelectronic device shifts to shorter wavelength recently [12,13] and thus, band-gap widening of the ZnO film is key issue, which should be resolved for employment of ZnO-based TCO in UV range optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%